RELEVANSI NILAI-NILAI PANCASILA DALAM MEMBANGUN KESADARAN KEWARGANEGARAAN MAHASISWA - Kurniawan Kurniawan; Muhammad Harapan Harahap; Abd Rahman Rusydi Hasibuan; Nur Hakima Akhirani (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
The main issue in this study is the decline in civic awareness among college students, as evidenced by intolerant attitudes, a tendency to be easily provoked, and a lack of social concern. Many students view Pancasila merely as rote memorization that is irrelevant to daily life. The objective of this study is to analyze the relevance of Pancasila values in fostering civic awareness among students and to identify the factors that support and hinder their internalization. This study employs a literature review method using a descriptive qualitative approach. Data sources include books, scientific journals, and previous research findings. Data analysis was conducted using content analysis techniques. The results indicate that the values of Pancasila remain highly relevant to students’ lives provided they are conveyed in a contextual and practical manner. Supporting factors for internalization include faculty role modeling, participatory learning methods, and student organizations. Meanwhile, inhibiting factors include the influence of foreign cultures, a lack of role models among public figures, and limited opportunities for discussion. In conclusion, Pancasila remains relevant but requires innovative teaching strategies.